2013
DOI: 10.4102/ajlm.v2i1.77
|View full text |Cite
|
Sign up to set email alerts
|

Setting up a structured laboratory mentoring programme

Abstract: IntroductionLaboratory mentoring programmes can be an important vehicle to establish and solidify quality management systems and help laboratories achieve accreditation goals. Different mentoring approaches have been used with varying levels of success. The authors provide a guide to implementing a structured laboratory mentorship programme based on their practical field experience.MethodThe study is based on experience in Lesotho as well as subsequent roll out of a similar approach in the other African countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 7 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…The standard mentorship model is described in detail elsewhere 14 and is based on mentors spending periods of time in laboratories to guide and oversee the quality systems improvement process. Six in-country, practising laboratory professionals were trained as mentors and completed the SLMTA Training-of-Trainers curriculum.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…The standard mentorship model is described in detail elsewhere 14 and is based on mentors spending periods of time in laboratories to guide and oversee the quality systems improvement process. Six in-country, practising laboratory professionals were trained as mentors and completed the SLMTA Training-of-Trainers curriculum.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…Our LQSI approach using a full-time staff of embedded quality improvement mentors has proven highly effective in implementing a quality management system in a large number of hospital laboratories in a relatively short period. Others have demonstrated that mentorship assists laboratories to implement quality improvement activities 23 , 24 , 31 . However, we have shown how the regular presence of fully dedicated mentors and a detailed quality management system action plan in the local language improves the rate of quality management system implementation.…”
Section: Discussionmentioning
confidence: 63%
“…The structured peer-to-peer, side-by-side mentorship approach was used to impart knowledge and expertise from the mentor to the laboratory staff following set guidelines. 13,14 Two additional mentors were assigned to BRHL, alternating supervisory visits and working with all staff members to implement a change in culture and address gaps. ISO 15189, the SLIPTA checklist and the SLMTA toolkit were the primary tools used for follow-up.…”
Section: Research Methods and Designmentioning
confidence: 99%